,,Am besten ... Dichter und Arzt zusammen". Zu Elias Canettis therapeutischem Literaturverständnis - Przybecki, Marek (Studia Germanica Posnaniensia, 2018)
This essay is an attempt at a methodological rehabilitation of semiotically conceived biography of the writer which is very often received by the readers parallelly to the fundamental writings - more or less legible "text". In the case of Canetti the legibility of this "text" is magnified by the fact that the researcher has here at his disposal a thick. volume - author's autobiography. The essay traces the sacramental formula quoted in the title and coming from the writer's mother's mouth, and as it appears this opinion was to shape a therapeutic vision of Canetti's literature. Literature as a form of social therapy - at this point both Canetti's "texts": the poetic and existential one converge.